2014
DOI: 10.1136/bmj.g1340
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion of deep vein thrombosis using the Wells rule in clinically important subgroups: individual patient data meta-analysis

Abstract: Objective To assess the accuracy of the Wells rule for excluding deep vein thrombosis and whether this accuracy applies to different subgroups of patients.Design Meta-analysis of individual patient data. Data sources Authors of 13 studies (n=10 002) provided their datasets, and these individual patient data were merged into one dataset.Eligibility criteria Studies were eligible if they enrolled consecutive outpatients with suspected deep vein thrombosis, scored all variables of the Wells rule, and performed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
162
2
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(181 citation statements)
references
References 41 publications
10
162
2
7
Order By: Relevance
“…Primary disease was classified into four categories: cancer bearing,6 infection,7 trauma,8 and others. These primary diseases were considered to affect the ED assessment because each is associated with positive D‐dimer results 6, 7, 8. Death during hospitalization was considered to indicate a severe disorder and was treated as a confounder for both variables and outcomes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary disease was classified into four categories: cancer bearing,6 infection,7 trauma,8 and others. These primary diseases were considered to affect the ED assessment because each is associated with positive D‐dimer results 6, 7, 8. Death during hospitalization was considered to indicate a severe disorder and was treated as a confounder for both variables and outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…In the differential diagnosis for the positive D‐dimer, we defined D‐dimer‐related diseases as DVT or pulmonary embolism,6, 10 aortic dissection,11 disseminated intravascular coagulopathy,12 and others. Documentation data were collected in a sentence, and two authors, D.T.…”
Section: Methodsmentioning
confidence: 99%
“…A Tabela 1 detalha o escore de Wells para TVP em pacientes sintomáticos. A reprodutibilidade e o desempenho do escore foram amplamente pesquisados, sendo o escore aplicado especialmente na avaliação de TVP em atendimentos ambulatoriais [8][9][10] .…”
Section: Introductionunclassified
“…To start with, the use of clinical decision rules in combination with D-dimer assays has not been evaluated in large cohorts for this specific clinical setting. [6][7][8] Furthermore, it has been shown that ultrasound abnormalities persist in ;80% of patients 3 months and in 50% of patients 1 year after initial DVT diagnosis, despite adequate anticoagulation. 9 Because a sonographer cannot determine whether incompressibility of a specific vein segment is caused by a new DVT or residual thrombosis, the usefulness of CUS in a patient with suspected ipsilateral recurrent DVT is questionable.…”
Section: Casementioning
confidence: 99%